Comparison of clinical characteristics between SARS-CoV-2 Omicron variant and Delta variant infections in China - Li, Qinggang; Liu, Xiaorui; Li, Lei; Hu, Xiaobo; Cui, Guangying; Sun, Ranran; Zhang, Donghua; Li, Juan; Li, Yonghong; Zhang, Yong; Shen, Shen; He, Ping; et al. (Frontiers in Medicine, 2022)
Background The continued 'evolution' of Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has led to the emergence of the Omicron variant after the Delta variant, resulting in a significant increase in the number of people with COVID-19. This increase in the number of cases continues to have a significant impact on lives. Therefore, a more detailed understanding of the clinical characteristics of Omicron infection is essential. Methods Using medical charts, we extracted clinical information for 384 patients infected with the Omicron variant in Anyang City, Henan Province, China. Epidemiology and clinical characteristics were compared with a cohort of people infected with the Delta variant in Zhengzhou in 2021. Findings Common initial symptoms at onset of illness were cough (240 [63%]), expectoration (112 [29%]), fever (96 [25%]), nasal congestion (96 [25%]) and myalgia or fatigue (30 [6%]). In patients with the Omicron variant, levels of total cholesterol, low-density lipoprotein and creatinine increased in 52 (14%), 36 (9%) and 58 (15%) patients, respectively, compared with patients with the Delta variant (one [1%], one [1%] and two [2%]). Levels of triglycerides and high-density lipoprotein also increased. In patients with the Omicron variant, specific gravity and the erythrocyte sedimentation rate were increased in 115 (30%) and 81 (21%) patients, and serum levels of complement 3 decreased in 93 (41%). Results Compared with patients infected with Delta, no major differences in initial clinical symptoms were identified in patients infected with Omicron. However, dyslipidemia and kidney injury were much more severe in patients with the Omicron variant, and the erythrocyte sedimentation rate was increased. Due to decreased levels of complement 3, the immunity of patients with the Omicron variant was weak.